PENGEMBANGAN NILAI FILSAFAT DALAM MENGIMPLEMENTASIKAN ILMU BAHASA INDONESIA - Roni Subhan; Retno Ayu Wulandari (Sanjiwani: Jurnal Filsafat, 2025)
In Indonesia, the use of Bahasa Indonesia by all its citizens is an efficient means of communication to convey messages. The language is dominant in daily activities, which is especially important in an era of scientific and technological advancement that emphasizes specialization, because studying the views of scientists can help humans realize their limitations and avoid intellectual arrogance. Philosophy has a role as a carrier of values for society, focusing on learning that is relevant to everyday life. As part of value education, philosophy can be a tool to nurture habits of thought and reflect on the values of life. However, the existence of the Indonesian language as the glue of the nation seems to be neglected due to the abundance of new vocabulary, including abbreviations and foreign terms. To philosophize is to explore deeply and earnestly. It is knowledge that reaches the root of everything according to ratio. It summarizes reality as a whole, especially human existence and purpose. Philosophy of science aims to investigate the various sources of knowledge, from theories of language acquisition based on views such as behaviorism or cognitivism, which basically stem from philosophical statements that were once delivered by prominent philosophers.